Resolving Intrastate Conflicts of Laws: The Example of the Federal Arbitration Act - Andrew D. Bradt (Washington University Law Review, 2015)
Choice-of-law analysis is typically thought of as confined to the multistate setting. This is a mistake. To the contrary, conflicts often appear between statutes of a single state. Unfortunately, courts do not see these cases as “choice-of-law” cases. They see them only as problems of statutory interpretation and ignore conflicts of laws instead of resolving them, either by construing the conflicting statutes independently or applying a canon of construction. Here, I examine the benefits of importing choice-of-law tools—particularly the tools of governmental-interest analysis—into the resolution of intrastate conflicts of laws. When two laws promulgated by the same sovereign clash, governmental-interest analysis is a promising approach to resolve the conflict. It is promising not only because it offers a path toward more rational results, but also because it highlights conflicts, requires courts to make explicit their policy preferences, and potentially prompts legislative dialogue. After suggesting how interest analysis might work to resolve intrastate conflicts of laws, I turn to a specific example of such a conflict: the Supreme Court’s decision last term in American Express Co. v. Italian Colors Restaurant, in which the Court held, 5–4, that the Federal Arbitration Act commanded enforcement of an arbitration clause that rendered the defendant’s alleged antitrust violations practically unenforceable. Although the Court did not say so, Italian Colors was a choice-of-law case. Use of choice-of-law methodology would have laid bare the conflict and provided a more direct path to its resolution. Italian Colors, therefore, provides an example of the opportunities available in using choice-of-law analysis to resolve intrastate conflicts.
Keywords: American Express Co. v. Italian Colors Restaurant; Choice of Law; Conflict of Laws; Arbitration; Federal Arbitration Act